Field‐calibrated model of melt, refreezing, and runoff for polar ice caps: Application to Devon Ice Cap. Issue 9 (29th September 2014) - Morris, Richard M.; Mair, Douglas W. F.; Nienow, Peter W.; Bell, Christina; Burgess, David O.; Wright, Andrew P.
Abstract Understanding the controls on the amount of surface meltwater that refreezes, rather than becoming runoff, over polar ice masses is necessary for modeling their surface mass balance and ultimately for predicting their future contributions to global sea level change. We present a modified version of a physically based model that includes an energy balance routine and explicit calculation of near‐surface meltwater refreezing capacity, to simulate the evolution of near‐surface density and temperature profiles across Devon Ice Cap in Arctic Canada. Uniquely, our model is initiated and calibrated using high spatial resolution measurements of snow and firn densities across almost the entire elevation range of the ice cap for the summer of 2004 and subsequently validated with the same type of measurements obtained during the very different meteorological conditions of summer 2006. The model captures the spatial variability across the transect in bulk snowpack properties although it slightly underestimates the flow of meltwater into the firn of previous years. The percentage of meltwater that becomes runoff is similar in both years; however, the spatial pattern of this melt‐runoff relationship is different in the 2 years. The model is found to be insensitive to variation in the depth of impermeable layers within the firn but is very sensitive to variation in air temperature, since the refreezing capacity of firn decreases with increasing temperature. We highlight that the sensitivity of the ice cap's surface mass balance to air temperature is itself dependent on air temperature.